Analysis of electric filters for cleaning the air environment of production premises - A. G. Vozmilov; R. Yu. Ilimbetov; S. A. Panishev; A. A. Lisov (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE: The problem of hazardous working conditions in Russia attracts attention due to an increase in the proportion of workers exposed to negative impacts on their health. Of particular interest is the analysis of the air environment as the main factor influencing human health. 32.2% of workers in hazardous working conditions are exposed to airborne factors, which leads to occupational diseases. To reduce the harmful effects of the air, it is necessary to clean it from harmful components. A promising device for air purification is an electric precipitator.PURPOSE: The study is aimed at selecting and optimizing electric precipitators for air purification in industrial premises. The goal is to determine the most effective design of an electric precipitator for cleaning the air environment of industrial premises.METHODS: The analysis is carried out on the basis of statistical data, the results of studies of electric precipitators of various designs for cleaning the air from dust, harmful gases and microorganisms. The results are used for comparative analysis.RESULTS: The study reveals that different designs of electrostatic precipitators demonstrate different effectiveness in air purification depending on the type of design. The design of corona electrodes affects ozone generation. It has been established that two-zone electrostatic precipitators with needle corona electrodes on the negative corona can significantly reduce ozone emissions. Wet electrostatic precipitators have regeneration, and the presence of several stages increases the cleaning efficiency. Electrostatic filters do not generate ozone and can be used in explosive low-volume areas.CONCLUSION: The study confirms that the choice of electrostatic precipitator should depend on the specifics of production and the volume of the room. For explosive environments, electrostatic precipitators should be preferred, while for large areas, a wet multi-stage electrostatic precipitator is recommended. Electrostatic precipitators-ozonizers can be effective for air disinfection. Summarizing the results allows us to conclude that it is important to choose the appropriate type of electrostatic precipitator to ensure optimal air conditions for the safety of workers.